Teachers’ and Principals’ Perceptions of School Administrative Staff Performance: A Case Study of UPT SDN 106 Manangalu, Burau District - Wahyuti, Sri; Said, Rusdin; Kuddus, Muhammad (The Future of Education Journal, 2026)
This study aims to explore teachers’ and principals’ perceptions of the performance of School Administrative Staff (TAS) at UPT SDN 106 Manangalu, Kecamatan Burau, as well as to identify the key factors influencing these perceptions. The research employed a descriptive qualitative approach with data collected through questionnaires, interviews, and observations. A total of 21 respondents, consisting of teachers and the principal, participated in the study. Data analysis referred to Robbins and Judge’s (2019) theory of perception and Bernardin and Russell’s (2013) performance theory, covering five main aspects: quality of administrative services, discipline and attendance, communication and teamwork, use of information technology, and work effectiveness. The findings indicate that teachers’ and principals’ perceptions of TAS performance are generally in the good to very good category. The highest score was recorded in the quality of administrative services (average 3.51 or 87.75%), while the lowest was in the use of information technology (3.00 or 75%) and work effectiveness (3.01 or 75.25%). The most influential factors shaping positive perceptions are effective communication and teamwork, mastery of information technology, and overall work effectiveness in supporting school operations. In conclusion, TAS are perceived to perform their administrative duties well, showing discipline and professionalism. However, improvements are still needed in time discipline, digital technology utilization, and initiative in task completion. This research is expected to provide valuable insights for schools and policymakers in enhancing TAS performance to better meet the demands of school administration in the digital era.